Legal Protection Of Health Worker In The Medical Malpractice Lawsuit In Banjarmasin - Yulia Audina Sukmawan; Akhmad Khisni (Jurnal Daulat Hukum, 2019)
Doctor and patient relationship is based on trust, it could turn into a medical malpractice lawsuit. Medical malpractice lawsuit due to the weakness in building communication cause harm to patients and health workers. Health workers are required to further improve the professionalism, quality, transparency, which leads to more excellent service in accordance with established standards. The problems are: What is the process for resolving cases of medical malpractice in Banjarmasin city, and how the legal protection of medical personnel in the event of criminal acts of medical malpractice in Banjarmasin. The purpose describes the process of settlement of medical malpractice and legal protection of medical personnel in the city of Banjarmasin. Benefits of reference enrich malpractice settlement process and provide knowledge of the legal protection of medical personnel in the city of Banjarmasin. The method used legal approach juridical empirical research specifications descriptive analytical data sources and data types using the type of primary data, secondary data and tertiary data collection methods used by interview, literature, study of documents, data analysis methods are qualitatively presented descriptively. The problem was analyzed using the theory of legal protection and legal liability. So health workers who have been carrying out duties in accordance with professional standards and SPO are entitled to legal protection.Keywords: Legal Protection; Health Workers; Medical Malpractice.